2017
DOI: 10.1007/s12640-017-9748-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protective Effects of Sarains on H2O2-Induced Mitochondrial Dysfunction and Oxidative Stress in SH-SY5Y Neuroblastoma Cells

Abstract: Sarains are diamide alkaloids isolated from the Mediterranean sponge Haliclona (Rhizoniera) sarai that have previously shown antibacterial, insecticidal and anti-fouling activities. In this study, we examined for the first time the neuroprotective effects of sarains 1, 2 and A against oxidative stress in a human neuronal model. SH-SY5Y cells were co-incubated with sarains at concentrations ranging from 0.01 to 10 μM, and the well-known oxidant hydrogen peroxide at 150 μM for 6 h and the protective effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…It has been reported that oxidative stress plays a crucial role in PD (Jenner, 2003;Puspita et al, 2017). Some natural products were reported to prevent oxidative stress in H 2 O 2 -treated SH-SY5Y cells (Alvarino et al, 2017;De Oliveira et al, 2017;De Oliveira et al, 2018). However, the effects of a-cyperone in H 2 O 2 -treated SH-SY5Y cells have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxidative stress plays a crucial role in PD (Jenner, 2003;Puspita et al, 2017). Some natural products were reported to prevent oxidative stress in H 2 O 2 -treated SH-SY5Y cells (Alvarino et al, 2017;De Oliveira et al, 2017;De Oliveira et al, 2018). However, the effects of a-cyperone in H 2 O 2 -treated SH-SY5Y cells have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of laxaphycins on cell metabolic activity was evaluated by MTT (3-(4, 5-dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) assay [27,49]. SH-SY5Y cells were cultured in 96-well plates and treated with compounds at concentrations ranging from 0.001 to 10 µM for 24 h. Next, cells were rinsed three times and incubated for 1 h with MTT (500 µg/mL) dissolved in saline buffer.…”
Section: Metabolic Activity Evaluationmentioning
confidence: 99%
“…∆Ψ m was evaluated with TMRM assay as previously described [49]. SH-SY5Y cells were seeded in 96-well plates at 5 × 10 4 cells per well.…”
Section: Mitochondrial Membrane Potential Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…H2O2-induced oxidative stress reduced glutathione level [25], induced DNA damage and apoptosis in cultured cells [26]. H2O2 action is accompanied by mitochondrial depolarization, aggregation, and cytochrome C release [27], and increased MAPK and p38 [28] in other cells and SH-SY5Y cells [29].…”
Section: Oxyresveratrol Content In Puag-haadmentioning
confidence: 99%